2016
DOI: 10.1159/000454916
|View full text |Cite
|
Sign up to set email alerts
|

Why Almost Always <b><i>Animals</i></b>? Ranking Fluency Tasks for the Detection of Dementia Based on Receiver Operating Characteristic (ROC) and Quality ROC Analyses

Abstract: Background/Aims: Category fluency tasks have been widely used to assess cognitive functioning in both clinical and experimental environments as an index of cognitive and psycholinguistic dysfunctions in dementia. Typically, a reduced group of semantic categories has been selected for neuropsychological assessment (e.g., animals, fruits or vegetables), although empirical support for the prevalence of one category among others is absent in the literature. Methods: We provide an empirical evaluation of the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Also, it has been shown to discriminate people with mild cognitive impairment (MCI) and dementia from people with normal aging (e.g., Choi, 2008 ; cf. Moreno-Martínez et al, 2017 ; Oh et al, 2019 ). In people with AD, animal fluency is often more impaired than letter fluency (e.g., Monsch et al, 1992 ; Henry and Crawford, 2004 ; Henry et al, 2004 ), though the opposite pattern has also been reported (e.g., Fisher et al, 2004 ; Laws et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown to discriminate people with mild cognitive impairment (MCI) and dementia from people with normal aging (e.g., Choi, 2008 ; cf. Moreno-Martínez et al, 2017 ; Oh et al, 2019 ). In people with AD, animal fluency is often more impaired than letter fluency (e.g., Monsch et al, 1992 ; Henry and Crawford, 2004 ; Henry et al, 2004 ), though the opposite pattern has also been reported (e.g., Fisher et al, 2004 ; Laws et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this apparent language dominance imbalance might also be caused by the different letters and categories used in the English and French versions of the verbal fluency task. Research has suggested that speakers tend to produce more tokens overall in the "animals" category than in the "fruits" category (Moreno-Martínez et al, 2017;Gabrić and Vandek, 2020). Thus, the apparent language proficiency imbalance in favor of English might be caused by our use of an "easier" category in the testing of English proficiency.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Moreover, pathological populations may show deficits of different degrees on different SF categories or they may show normative deficits on one but not the other category. Several studies on SF in dementia and Alzheimer's disease have revealed that the extent of the deficit is dependent on the given category's size (Diaz et al 2004), while Moreno-Martínez et al (2017) and Neves et al (2020) found that although the animal fluency is by far the most commonly utilized SF task for research on dementia, other categories such as supermarket items, fruits, and vegetables are more sensitive in distinguishing healthy people from patients with dementia. On the other hand, Gabrić and Vandek (2020, in review) reported that patients with first-episode psychosis displayed deficient clustering on the categories animals, vegetables, and musical instruments but not on trees and fruits (cf.…”
Section: Category-specific and Letter-specific Effects On Verbal Fluency Performancementioning
confidence: 99%
“…While no subjects produced intrusions on the animal task, intrusions on the tree task were produced by seven subjects. We would like to note at this point that we were very careful in classifying responses as intrusions and that our criteria for intrusion classification were more lax (but nevertheless precise) compared to, for example, Moreno-Martínez et al (2017) who classified fruit trees (such as pear) as intrusions on the tree task. In our study, fruit trees were classified as legal because we found there was no reason to classify them as errors.…”
Section: Semantic Fluencymentioning
confidence: 99%